Incorporation and Remodeling of Structural Allografts in Acetabular Reconstruction: Multiscale, Micro-Morphological Analysis of 13 Pelvic Explants. (15th August 2018) - Butscheidt, Sebastian; Moritz, Menard; Gehrke, Thorsten; Püschel, Klaus; Amling, Michael; Hahn, Michael; Rolvien, Tim
Abstract : Background: Total hip arthroplasty (THA) is frequently accompanied by acetabular bone loss, which constitutes a major challenge in revision procedures. Structural allografts can be implanted to restore a stable osseous foundation for the acetabular prosthesis. As previous studies were limited to clinical data or included very few cases, the extent to which the graft bone is incorporated over time has remained unclear. Methods: Thirteen acetabula were retrieved post mortem, and the incorporation properties of the bone allografts were analyzed using a hierarchical approach of imaging techniques including contact radiography, high-resolution peripheral quantitative computed tomography (HR-pQCT), histological analysis of undecalcified specimens, and quantitative backscattered electron imaging (qBEI). The distance between the current allograft bone and host bone borders (i.e., current overlap) as well as the distance between the original allograft bone and host bone borders (i.e., total ingrowth) were assessed. Results: In 10 of 13 cases, the complete interface (100%) was characterized by direct contact and additional overlap of the allograft bone and host bone, while the remaining 3 cases demonstrated direct contact along 25% to 80% of the interface. The allograft bone showed an intact trabecular structure and significantly higher mineralization compared with the host bone. The mean current overlap (and standard deviation) was 2.3 ± 1.0 mm, with a maximum of 5.3 ± 2.4 mm. Importantly, the total ingrowth reached much further, to a mean of 7.2 ± 2.3 mm (maximum, 10.5 ± 4.0 mm). Neither the time that the allograft was in situ nor the degree of contact between the host and allograft bone correlated with the current overlap and the time in situ did not correlate with total ingrowth. Conclusions: This study showed bone remodeling with subsequent interconnection of the host and allograft bone along the majority of the interface, leading to adequate incorporation of the allograft. The lack of complete incorporation of the graft did not lead to graft collapse up to 22 years after revision surgery. Clinical Relevance: Our study provides the first systematic multiscale evaluation of successfully implanted structural allografts and forms the scientific basis for their clinical use in revision THA.